Antiskid easy-to-clean ceramic tile as well as preparation method and application thereof
Through the design of microporous glaze and polishing process, the problem of difficult balance between anti-skid and anti-fouling properties of existing anti-skid ceramic tiles has been solved, and the excellent anti-skid performance and easy cleaning of the ceramic tiles have been achieved, reaching the anti-skid level of European standard R10.
Patent Information
- Application Number
- CN202411297457.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-24
AI Technical Summary
It is difficult to balance the anti-slip performance and anti-slip performance of existing anti-slip tiles, and there are technical problems such as easy to hide dirt, difficulty in cleaning, unscientific glaze formula, and unstable firing process.
通过设计多种形成微孔釉面的釉料,调整石粉、熔块、黏土和助剂的比例,使烧制后的瓷砖表面形成孔径在40-100μm之间的微孔,结合抛光工艺,使 The micro -hole glazed surface is half -cut, which improves anti -slip and pollution -proof performance.
The excellent non -slip performance and easy to clean the surface of the tile, the non -slip level reaches the European standard R10, and it can effectively prevent the hidden dirt and such as oil and dust during cleaning, and reduce the maintenance cost.
Smart Images

Figure CN119350062A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic tiles, and in particular to a non-slip and easy-to-clean ceramic tile and a preparation method and application thereof. Background Art
[0002] In the building materials floor tile market, anti-slip performance has always been an important consideration for customers when purchasing tiles. Traditional anti-slip tiles, such as antique tiles, frosted tiles and concave-convex mold tiles, mainly achieve anti-slip effects by increasing the roughness of the tile surface. The design idea of these tiles is to increase the friction between the shoe surface and the shoe surface by increasing the roughness of the glaze or forming dense capillary holes, thereby achieving an anti-slip function. However, while this design method brings about an anti-slip effect, it also causes a series of technical problems.
[0003] First of all, although the rough and raised surface can significantly increase the friction coefficient, its complex texture structure easily harbors dirt and becomes a breeding ground for bacteria. It is also difficult to completely remove it during daily cleaning, resulting in poor anti-fouling effect and high maintenance costs.
[0004] Secondly, although the capillary pore design can block large particles of dirt and sewage to a certain extent, its ability to prevent liquid penetrating dirt such as oily pens and ink is limited.
[0005] In addition, traditional anti-slip tiles also have deficiencies in glaze formula and firing process. The choice of glaze formula directly affects the performance of tiles, such as wear resistance, anti-slip, anti-fouling, etc. However, many anti-slip tiles on the market lack scientific and innovative glaze formulas, resulting in the production of tiles that are difficult to achieve optimal performance. At the same time, the control of the firing process is also crucial, and slight changes in factors such as temperature and time may have a significant impact on the final performance of the tile.
[0006] In summary, it is difficult to strike a balance between the anti-slip performance and the anti-fouling performance of existing anti-slip tiles, and there are technical problems such as easy to hide dirt, difficult to clean, unscientific glaze formula, unstable firing process, etc. These problems not only affect the customer's experience, but also limit the further development of anti-slip tiles in the market. Therefore, it is particularly important to develop a tile that has both excellent anti-slip performance and is easy to clean.
[0007] To this end, the present application provides a non-slip and easy-to-clean tile and a preparation method and application thereof. Summary of the invention
[0008] The present application provides a non-slip and easy-to-clean tile and a preparation method and application thereof. By designing a variety of glazes for forming the microporous glaze, and adjusting the proportions of the various components in the glaze, such as stone powder, frit, clay and additives, micropores with a specific pore size range are formed on the surface of the tile after firing, and the diameter of the micropores is controlled between 40-100μm. Therefore, the microporous glaze not only ensures anti-fouling properties, but also avoids the disadvantage that small-pore tiles are difficult to clean.
[0009] The technical solution adopted by this application to solve its technical problem is:
[0010] In a first aspect, the present application provides a non-slip and easy-to-clean tile, comprising a body, on which a microporous glaze is provided, wherein the diameter of micropores in the microporous glaze is 40-100 μm.
[0011] In some embodiments, the microholes are polished to a semi-cut state.
[0012] In some embodiments, the glossiness of the anti-slip and easy-to-clean tiles is 28-35°.
[0013] In some embodiments, the glaze for forming the microporous glaze surface includes the following raw materials in parts by weight:
[0014] 50-55 parts of stone powder, 32-35 parts of frit, 10-12 parts of clay, and 8-9 parts of additives.
[0015] In some embodiments, the glaze for forming the microporous glaze surface includes the following raw materials in parts by weight:
[0016] 93-96 parts of non-porous glaze powder and 5-6 parts of thermal decomposition material.
[0017] In some embodiments, the stone powder includes at least one of potassium feldspar, sodium feldspar, calcined talc, dolomite, and quartz; and the clay is kaolin.
[0018] In some embodiments, the thermally decomposable material is polymethyl methacrylate.
[0019] In a second aspect, the present application provides a method for preparing non-slip and easy-to-clean tiles, comprising the following steps:
[0020] S1. Prepare glaze for forming the microporous glaze
[0021] According to the weight composition of the glaze for forming the microporous glaze, the raw materials are mixed, ball-milled, and printing paste and printing oil are added; ball-milled again and the specific gravity is adjusted, and the mixture is sieved;
[0022] S2. Glazing
[0023] Using screen printing, the prepared microporous glaze is evenly printed on the surface of the body to obtain a glazed body;
[0024] S3. Firing
[0025] The glazed body is sent into the kiln for firing;
[0026] S4. Polishing
[0027] After firing, the tiles are polished to a semi-cut state.
[0028] In some embodiments, in step S1, the raw materials are mixed and ball-milled, and the fineness after ball-milling reaches 325-350 mesh.
[0029] On the third aspect, the present application provides an application of anti-slip and easy-to-clean tiles, which are used as decoration materials in the fields of home decoration, commercial places, industry, and public facilities.
[0030] The beneficial effects of this application are:
[0031] 1. The anti-slip and easy-to-clean ceramic tile described in the present application is designed with a variety of glazes for forming the microporous glaze surface. By adjusting the proportions of the various components in the glaze, such as stone powder, frit, clay and additives, micropores with a specific pore size range are formed on the surface of the ceramic tile after firing. The diameter of the micropores is controlled between 40-100 μm. Therefore, the microporous glaze surface not only ensures anti-fouling properties, but also avoids the disadvantage that small-pore ceramic tiles are difficult to clean.
[0032] 2. The anti-skid and easy-to-clean ceramic tile described in the present application adopts a polishing process to expose most of the microporous holes on the microporous glaze with the maximum radius (forming semicircular pits), presenting a semi-cut state, which not only increases the transparency of the ceramic tile surface, but also reduces the glossiness of the ceramic tile surface through the light scattering effect formed by the porous holes, so that the glossiness is maintained at 28-35°, thus presenting a soft and non-glaring light feeling. At the same time, these dense semicircular pits also enhance the anti-skid performance of the ceramic tile, and by increasing the static friction coefficient (reaching 0.67-0.7) and excellent adsorption, the anti-skid grade of the ceramic tile reaches the European standard R10.
[0033] 3. The anti-slip and easy-to-clean ceramic tile described in this application successfully solves the shortcomings of traditional anti-slip ceramic tiles in anti-fouling performance by optimizing the glaze formula and polishing process, and develops a ceramic tile product that is both anti-slip and easy to clean.
[0034] 4. The anti-slip and easy-to-clean ceramic tile described in the present application not only has excellent anti-slip performance, but can also prevent the hiding of dirt such as oil and dust to a large extent, making cleaning work simple and quick. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0036] Figure 1 This is a microscope image of the surface holes of the non-slip and easy-to-clean ceramic tile described in Example 3;
[0037] Figure 2 This is a comparison chart of the anti-slip and easy-to-clean ceramic tile described in Example 3 subjected to an oil-based pen anti-fouling test (before and after);
[0038] Figure 3 This is the observation of the holes on the surface of the tile under a microscope;
[0039] Figure 4 This is a schematic diagram of the anti-slip and easy-to-clean tiles described in this application. DETAILED DESCRIPTION
[0040] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.
[0041] As used herein, "and / or" includes the term of any and all combinations of one or more associated listed items. The terms used herein are only used to describe specific embodiments and are not intended to limit the present invention. As used herein, the singular forms "a", "an", "an" and "the" are also intended to include the plural forms, unless the context clearly indicates otherwise. It is further understood that "including", when used in this specification, specifies the stated features, integers, steps, operations, elements and / or compositions, but does not exclude the existence or addition of one or more other features, integers, steps, operations, elements, compositions and / or combinations thereof.
[0042] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. It is further understood that terms, such as defined in commonly used dictionaries, are interpreted in accordance with their meanings in the context of the relevant art and are not in an idealized or overly formal sense unless explicitly so defined herein.
[0043] The exemplary invention described herein may appropriately lack any one or more element limitations that are not specifically disclosed herein. Therefore, the terms "comprise", "include", "contain", etc. should be understood broadly and non-restrictively. In addition, the terminology used herein is used as a description, not a limitation, and it is unintentional to use these terminology expressions that do not include any equivalent characteristics, but only describe some of their characteristics, but various modifications are possible within the scope of the present invention according to the rights. Therefore, although the present invention has been specifically disclosed by preferred embodiments and optional features, the modifications disclosed herein to embody the changes of the present invention may be recorded by those skilled in the art, and such modifications and changes will be considered to be within the scope of the present invention.
[0044] Terminology explanation:
[0045] Ball milling is a material processing technology that crushes and mixes materials through grinding media (such as steel balls, ceramic balls, etc.) in a rotating or vibrating cylinder. In the preparation of ceramic glazes, ball milling is usually used to refine the raw materials to the required particle size range to increase the uniformity and activity of the raw materials and promote subsequent chemical reactions and physical mixing.
[0046] Green body refers to the semi-finished product that has not been sintered after the pressing and molding process in the production process of ceramic products. Green body is usually made of ceramic raw materials (such as clay, quartz, feldspar, etc.) through mixing, molding (such as pressing, grouting, etc.). In the production of ceramic tiles, green body is the basis of the final product, on which various glazes will be applied and sintered to obtain finished ceramic tiles with decorative and usable performance.
[0047] At present, the inventors have found that the roughness of tiles can be understood from two aspects:
[0048] 1. The degree of roughness and protrusion of the glaze surface (the roughness and protrusion affect the friction coefficient);
[0049] 2. The density of capillary holes in the glaze (the holes will form a small enclosed space with the shoe upper, acting as a suction cup).
[0050] The rough and raised surface is easy to hide dirt and grime, making it difficult to clean. In contrast, the capillary pores have a certain degree of anti-pollution ability for large particles of dirt and sewage, but are more likely to be stuck to liquid-penetrating dirt such as oily pens and inks, making them difficult to clean.
[0051] In the experimental analysis of the holes that are contaminated by dirt, it was found that: no matter it is a porous glaze or a glaze with low porosity, there is a certain pattern in the holes that are contaminated by oily pens (after the anti-fouling test, observe under a microscope) - Anti-fouling test: use an oily pen to cover the entire brick surface area, wait for 5 minutes for the ink to dry, then scrub with a detergent, repeat the above operation three times, observe the blue spots that cannot be cleaned, and if there are obvious blue spots / bluish when observed at a distance of 25 cm, the anti-fouling test fails.
[0052] like Figure 3 As shown, from the microscope image, we can see that blue spots will not appear in holes smaller than 7μm, and blue spots will not appear in holes larger than 40μm.
[0053] Therefore, when the capillary pores are smaller than 7μm, the ink of the oil pen cannot penetrate into the pores; when the capillary pores are between 7-40μm, the ink of the oil pen can penetrate into the pores and cannot be scrubbed clean with a detergent; when the capillary pores are larger than 40μm, the ink of the oil pen can penetrate into the pores and can be easily scrubbed clean with a detergent.
[0054] In order to solve the technical problems that it is difficult to strike a balance between the anti-slip performance and the anti-fouling performance of existing anti-slip tiles, and that they are easy to harbor dirt and grime, difficult to clean, have unscientific glaze formulas, and unstable firing processes, the present application provides an anti-slip and easy-to-clean tile, comprising a green body, on which a microporous glaze surface is provided, wherein the diameter of the micropores in the microporous glaze surface is 40-100μm.
[0055] like Figure 4 As shown, when the diameter of the micropores in the microporous glaze is between 40-100 μm, the ink of liquids such as oily pens can penetrate and can be easily wiped clean by a detergent, while also providing a good anti-slip effect.
[0056] When the micropore diameter exceeds 100μm, larger holes are more likely to become places for dirt and grime to hide, especially for fine dust and liquid stains. The gloss and texture of the tile surface may be affected. Holes that are too large may cause the gloss to decrease too much, affecting the appearance.
[0057] When the micropore diameter is less than 40μm, the anti-slip effect may be weakened because the holes are too small to provide sufficient roughness to increase the static friction coefficient; holes in the range of 7-40μm may cause stains that are difficult to clean. Although holes smaller than 7μm will not cause stains, they have limited contribution to anti-slip and visual effects.
[0058] In some embodiments, the micropores are in a semi-cut state after polishing; the semi-cut state is a surface morphology between fully cut and uncut. Specifically, it means that during the polishing process, by controlling the strength, speed and number of the polishing module, the micropore structure on the surface of the tile is neither too smooth to lose the anti-slip performance, nor too rough to affect the appearance and cleanability, but reaches a delicate balance.
[0059] More specifically, in the half-cut state, the micropores on the surface of the tile are mostly exposed with the maximum radius, forming dense semicircular pits. These pits not only increase the surface roughness and improve the anti-slip performance, but also due to their larger openings and appropriate depth, it is not easy for dirt to accumulate in them, thereby improving the anti-fouling effect.
[0060] In some embodiments, the glossiness of the non-slip and easy-to-clean tiles is 28-35°. In the present application, tiles with a glossiness in the range of 28-35° have a relatively low surface glossiness, and light is more scattered on its surface rather than reflected by a mirror, making the surface of the tile look softer and less dazzling. In addition, the soft glossiness helps to create a warm and comfortable living or working environment, avoiding the glare problem that may be caused by high-gloss tiles.
[0061] In some embodiments, the glaze for forming the microporous glaze surface includes the following raw materials in parts by weight:
[0062] 50-55 parts of stone powder, 32-35 parts of frit, 10-12 parts of clay, and 8-9 parts of additives.
[0063] Specifically, the weight of the stone powder is 50-55 parts, for example, it can be any value among 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, and 55 parts. The weight of the frit is 32-35 parts, for example, it can be any value among 32 parts, 33 parts, 34 parts, and 35 parts; the weight of the clay is 10-12 parts, for example, it can be any value among 10 parts, 11 parts, and 12 parts; the weight of the additive is 8-9 parts, for example, it can be any value among 8 parts, 8.5 parts, and 9 parts.
[0064] More specifically, the stone powder is at least one of potassium feldspar, sodium feldspar, calcined talc, dolomite, and quartz stone; the clay is at least one of kaolin and washed kaolin; the additive is at least one of zinc oxide, barium carbonate, and sodium tripolyphosphate; the frit: Zhenshi glaze frit (Yuanda).
[0065] In the present application, by precisely controlling the ratio of each component in the glaze forming the microporous glaze, the glaze can form a specific glossiness (28-35°). This glossiness range makes the light on the surface of the tile evenly scattered, avoiding the glare caused by high glossiness, while maintaining sufficient brightness, making the tile visually softer and more comfortable.
[0066] In terms of anti-slip performance, the specific proportions of stone powder, frit, clay and additives help to form an appropriate microporous structure on the glaze. These micropores not only increase the surface roughness of the tiles, but also enhance the anti-slip effect through adsorption, especially in wet and slippery conditions, which can effectively improve walking safety.
[0067] In some embodiments, the glaze for forming the microporous glaze surface includes the following raw materials in parts by weight:
[0068] 93-96 parts of non-porous glaze powder and 5-6 parts of thermal decomposition material.
[0069] Specifically, the weight of the non-porous glaze powder is 93-96 parts, for example, it can be any value among 93 parts, 94 parts, 95 parts, and 96 parts; the weight of the thermal decomposition material is 5-6 parts, for example, it can be any value among 5 parts, 5.6 parts, and 6 parts.
[0070] Specifically, the non-porous glaze powder is 386 type Yuanda dense non-porous glaze, and the thermal decomposition material is polymethyl methacrylate.
[0071] More specifically, non-porous glaze powder mainly refers to a type of glaze powder with high density and almost no significant holes; non-porous glaze powder is not easy to form large holes during the firing process, but through mixing with other components and special process treatment, it can be induced to form the required microporous structure through heat treatment and other methods in subsequent processing. Non-porous glaze powder can be any of feldspar, quartz, and clay minerals.
[0072] In the present application, non-porous glaze powder and thermal decomposition material (such as polymethyl methacrylate, PMMA) are used. During the firing process, the thermal decomposition material will produce gas, thereby forming a microporous structure in the glaze layer. The diameter of these micropores is controlled within a certain range to achieve the expected anti-slip and anti-fouling effects.
[0073] The method for preparing the above-mentioned non-slip and easy-to-clean ceramic tile comprises the following steps:
[0074] S1. Prepare glaze for forming the microporous glaze
[0075] According to the weight composition of the glaze for forming the microporous glaze, the raw materials are mixed and wet ball milled, and the fineness is measured to reach 325-350 mesh after ball milling for 3-4 hours; printing paste and printing oil are added; ball milling again and adjusting the specific gravity to 1.55-1.58, and passing through a 100-mesh sieve;
[0076] S2. Glazing
[0077] Use the full-pass screen printing to evenly print the prepared microporous glaze on the surface of the body by three passes; obtain the glazed body and dry it;
[0078] S3. Firing
[0079] The glazed body is sent into the kiln for firing;
[0080] S4. Polishing
[0081] After firing, the tiles are polished using 15 groups of 1200 mesh elastic modules + 5 groups of 5000 mesh elastic modules + 20 groups of hard fiber modules + 20 groups of soft fiber modules to bring the tile surface to a semi-cut state.
[0082] In the present application, in step S1, wet ball milling is used to ensure the fineness of the glaze, which helps to form a uniformly distributed microporous structure during the firing process. These micropores can increase the roughness of the tile surface and improve the anti-slip performance; after adding printing paste and printing oil, ball milling is performed again and the specific gravity is adjusted to 1.55-1.58 to ensure that the glaze has appropriate fluidity and adhesion, which is beneficial to the subsequent glazing and firing process.
[0083] In the present application, in step S2, three passes of full-pass screen printing are performed to ensure that the glaze of the microporous glaze can be evenly covered on the surface of the body. The multi-pass printing method helps to reduce the uneven distribution of the glaze and improve the overall consistency and aesthetics of the tile. At the same time, multi-pass printing can accurately control the thickness of the glaze layer to ensure that it is within a suitable range. The appropriate glaze layer thickness not only helps to form an ideal microporous structure, but also improves the wear resistance and anti-slip performance of the tile.
[0084] In the present application, in step S3, during the firing process, micropores with a pore size in the range of 40-100 μm can be formed, thereby ensuring the anti-slip performance while avoiding the disadvantage of small-pore tiles being difficult to clean; during the firing process, certain components in the glaze (such as thermal decomposition materials) may decompose to produce gases, thereby forming tiny holes on the glaze surface, which help to improve the anti-slip and anti-fouling properties of the tiles.
[0085] The specific firing process is to put it into the kiln for firing, and the temperature control is:
[0086] Preheating stage zone, 270-344°C for 15 minutes;
[0087] Oxidation decomposition stage: 350-980°C for 16 minutes;
[0088] High temperature stage: 1000-1200℃ for 15 minutes;
[0089] High-fire insulation stage: 1100-1000℃ for 16 minutes;
[0090] Cooling stage zone, 598-200°C for 19 minutes.
[0091] In the present application, in step S4, the micropores on the surface of the tile are exposed with the maximum radius through polishing, forming dense semicircular pits, and reaching a semi-cut state. At the same time, the light scattering effect formed by the porous holes reduces the glossiness of the tile surface, keeping its glossiness at 28-35°, presenting a soft and non-glaring light feeling.
[0092] At the same time, the present application provides an application of anti-slip and easy-to-clean tiles, which are used as decoration materials in the fields of home decoration, commercial places, industry, and public facilities.
[0093] Specifically, in the field of home decoration, non-slip and easy-to-clean tiles are used in living rooms, kitchens, bathrooms, balconies and other floors to ensure the safety and cleanliness of the family living environment and effectively prevent falls caused by slippery floors. In the field of commercial places, non-slip and easy-to-clean tiles are suitable for crowded areas such as hotel lobbies, restaurants, shopping malls, supermarkets, etc. to keep the floors clean and safe. In the industrial field, non-slip and easy-to-clean tiles are used in factory workshops, warehouses, laboratories and other environments. They can cope with various complex ground conditions and pollutants to keep the work area clean and safe. In the field of public facilities, non-slip and easy-to-clean tiles are used in public places such as subway stations, railway stations, hospitals, and schools to ensure the safety and comfort of the public.
[0094] The anti-slip and easy-to-clean ceramic tiles described in the present application are further described through the following embodiments and comparative examples.
[0095] Example 1
[0096] The method for preparing the anti-slip and easy-to-clean ceramic tile comprises the following steps:
[0097] Select 600*600 billets for standby use;
[0098] Take 430g potassium feldspar + 500g sodium feldspar + 50g calcined talc + 75g dolomite + 50g barium carbonate + 150g zinc oxide + 600g Zhenshi glaze frit + 250g kaolin + 750g water + 7.5g sodium tripolyphosphate, ball mill for 3-4h and measure the fineness (325 mesh), add 1.1kg printing paste and 100g printing oil, ball mill for 1h and measure the specific gravity (1.55-1.58), pass through a 100-mesh vibrating sieve to obtain a glaze forming the microporous glaze surface;
[0099] On a 600*600 billet, three layers of microporous glaze are screen-printed, and after printing, it is dried; put into the kiln for firing, and the temperature control is as follows: preheating stage zone, 270-344℃ for 15 minutes; oxidation decomposition stage zone, 350-980℃ for 16 minutes; high temperature stage zone, 1000-1200℃ for 15 minutes; high fire insulation stage zone, 1100-1000℃ for 16 minutes; cooling stage zone, 598-200℃ for 19 minutes;
[0100] After firing, the tiles are polished using 15 groups of 1200-mesh elastic modules + 5 groups of 5000-mesh elastic modules + 20 groups of hard fiber modules + 20 groups of soft fiber modules to obtain non-slip and easy-to-clean tiles.
[0101] Example 2
[0102] The method for preparing the anti-slip and easy-to-clean ceramic tile comprises the following steps:
[0103] Select 600*600 billets for standby use;
[0104] Take 430g potassium feldspar + 500g sodium feldspar + 50g calcined talc + 75g dolomite + 50g barium carbonate + 150g zinc oxide + 800g Zhenshi glaze frit + 250g kaolin + 750g water + 7.5g sodium tripolyphosphate, ball mill for 3-4h and measure the fineness (325 mesh), add 1.1kg printing paste and 100g printing oil, ball mill for 1h and measure the specific gravity (1.55-1.58), pass through a 100-mesh vibrating sieve to obtain a glaze forming the microporous glaze surface;
[0105] On a 600*600 billet, three layers of microporous glaze are screen-printed, and after printing, it is dried; put into the kiln for firing, and the temperature control is as follows: preheating stage zone, 270-344℃ for 15 minutes; oxidation decomposition stage zone, 350-980℃ for 16 minutes; high temperature stage zone, 1000-1200℃ for 15 minutes; high fire insulation stage zone, 1100-1000℃ for 16 minutes; cooling stage zone, 598-200℃ for 19 minutes;
[0106] After firing in the kiln, the tiles are polished using 115 groups of 1200-mesh elastic modules + 5 groups of 5000-mesh elastic modules + 20 groups of hard fiber modules + 20 groups of soft fiber modules to obtain non-slip and easy-to-clean tiles.
[0107] Example 3
[0108] The method for preparing the anti-slip and easy-to-clean ceramic tile comprises the following steps:
[0109] Select 600*600 billets for standby use;
[0110] Take 2kg Yuanda 386 model polishing glaze (1-2kg), add 0.1kg PMMA (100μm small ball), add 0.8kg water (0.5-1kg), ball mill for 3-4h, then measure the fineness (325 mesh), add 1.1kg printing paste and 100g printing oil, ball mill for 1h, then measure the specific gravity (1.55-1.58), pass through a 100-mesh vibrating sieve, and obtain a glaze forming the microporous glaze surface;
[0111] On a 600*600 billet, three layers of microporous glaze are screen-printed, and after printing, it is dried; put into the kiln for firing, and the temperature control is as follows: preheating stage zone, 270-344℃ for 15 minutes; oxidation decomposition stage zone, 350-980℃ for 16 minutes; high temperature stage zone, 1000-1200℃ for 15 minutes; high fire insulation stage zone, 1100-1000℃ for 16 minutes; cooling stage zone, 598-200℃ for 19 minutes;
[0112] After firing, the tiles are polished using 15 groups of 1200-mesh elastic modules + 5 groups of 5000-mesh elastic modules + 20 groups of hard fiber modules + 20 groups of soft fiber modules to obtain non-slip and easy-to-clean tiles.
[0113] Comparative Example 1
[0114] The method for preparing the anti-slip and easy-to-clean ceramic tile comprises the following steps:
[0115] Select 600*600 billets for standby use;
[0116] Take 2kg Yuanda 386 model polishing glaze (1-2kg), add 0.8kg water (0.5-1kg), ball mill for 3-4h, then measure the fineness (325 mesh), add 1.1kg printing paste and 100g printing oil, ball mill for 1h, then measure the specific gravity (1.55-1.58), pass through a 100-mesh vibrating sieve, and obtain the glaze on the glaze surface;
[0117] On a 600*600 billet, three layers of microporous glaze are screen-printed with a full-through mesh. After printing, the billet is dried and put into the kiln for firing. The temperature is controlled as follows: preheating stage, 270-344°C for 15 minutes; oxidation decomposition stage, 350-980°C for 16 minutes; high temperature stage, 1000-1200°C for 15 minutes; high fire insulation stage, 1100-1000°C for 16 minutes; cooling stage, 598-200°C for 19 minutes. After firing, the billet is polished with 15 groups of 1200 mesh elastic modules + 5 groups of 5000 mesh elastic modules + 20 groups of hard fiber modules + 20 groups of soft fiber modules to obtain non-slip and easy-to-clean tiles.
[0118] Comparative Example 2
[0119] The method for preparing the anti-slip and easy-to-clean ceramic tile comprises the following steps:
[0120] Select 600*600 billets for future use.
[0121] Take 460g potassium feldspar + 500g sodium feldspar + 50g calcined talc + 75g dolomite + 80g barium carbonate + 200g zinc oxide + 50g calcined alumina + 600g Zhenshi glaze frit + 250g kaolin + 750g water + 7.5g sodium tripolyphosphate, ball mill for 3-4h and measure the fineness (325 mesh), add 1.1kg printing paste and 100g printing oil, ball mill for 1h and measure the specific gravity (1.55-1.58), pass through a 100-mesh vibrating sieve to obtain a glaze material;
[0122] On a 600*600 billet, three layers of microporous glaze are screen-printed with a full-through mesh. After printing, the billet is dried and put into the kiln for firing. The temperature is controlled as follows: preheating stage, 270-344°C for 15 minutes; oxidation decomposition stage, 350-980°C for 16 minutes; high temperature stage, 1000-1200°C for 15 minutes; high fire insulation stage, 1100-1000°C for 16 minutes; cooling stage, 598-200°C for 19 minutes. After firing, the billet is polished with 15 groups of 1200 mesh elastic modules + 5 groups of 5000 mesh elastic modules + 20 groups of hard fiber modules + 20 groups of soft fiber modules to obtain non-slip and easy-to-clean tiles.
[0123] The ceramic tiles prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to the following performance tests, and the relevant test results are summarized in Table 1;
[0124] 1. Dry static friction coefficient, test the anti-slip performance according to the national standard method: "GB / T-37798-2019" static friction coefficient method;
[0125] 2. The anti-slip grade of the slope method shall be carried out in accordance with the anti-slip grade of the slope method of GB / T-37798-2019;
[0126] 3. Anti-fouling test: Use a blue oil pen to cover the entire brick surface area, wait for 5 minutes for the ink to dry, then scrub with hand washing powder, repeat the above operation three times, and observe the brick surface at a distance of 25cm. If there are obvious blue spots / bluish, the anti-fouling test fails.
[0127] 4. Appearance: visually check whether it affects the base color texture.
[0128] Table 1
[0129]
[0130] As can be seen from Table 1, in terms of anti-slip performance, the dry static friction coefficient of the tiles of Examples 1-3 ranges from 0.67 to 0.72, all reaching above 0.67, which indicates that the tiles of these examples have good anti-slip performance. According to the "GB / T-37798-2019" standard, the anti-slip grade of these tiles reaches R10, which is the highest grade in the anti-slip grade.
[0131] In terms of antifouling performance, the tiles of Examples 1-3 all performed well in the antifouling test, that is, after the tile surface area was painted with a blue oil pen, the ink could be cleaned by scrubbing without leaving any obvious traces. This shows that the microporous glaze of the tiles of Examples 1-3 effectively balances the anti-slip and anti-fouling performance. Figure 2 , a blank sample (blank 0) is used to compare whether the background color has changed; the tile of Example 3 before cleaning is painted with an oil pen, and the dirt pits are observed; after cleaning, it is found that there is no dirt under human eye observation; after cleaning, it is enlarged to verify that the local blue dots are the blue tone of the background color pattern, and the blue dots are not stuck in the pits.
[0132] In terms of appearance quality, the appearance test results of the tiles of Examples 1-3 showed that the base color and pattern of the tiles were not affected, maintaining a good visual effect.
[0133] The anti-skid performance of comparative example 1 is slightly lower than that of the embodiment, with a static friction coefficient between 0.65 and 0.68 and an anti-skid grade of less than R9. The anti-skid performance of comparative example 2 is even lower, with a static friction coefficient between 0.58 and 0.66 and an anti-skid grade of R9. In the anti-fouling test, a problem of blue spots in local areas appeared, and the appearance also showed uneven brightness and visible holes like "orange peel".
[0134] The raw materials or reagents used in the examples and comparative examples of the present invention are all purchased from mainstream manufacturers in the market. Those without indicating the manufacturer or concentration are all analytically pure raw materials or reagents that can be routinely obtained. As long as they can play the expected role, there is no special limitation.
[0135] The instruments and equipment used in this embodiment are all purchased from major manufacturers in the market, and there is no particular limitation as long as they can play the expected role. In this embodiment, if no specific technology or conditions are specified, the technology or conditions described in the literature in this field or the product instructions are used. The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention can also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.
Claims
1. A non-slip and easy-to-clean tile, comprising a body, characterized in that: The green body is provided with a microporous glaze surface, and the diameter of micropores in the microporous glaze surface is 40-100 μm.
2. The anti-slip and easy-to-clean tile according to claim 1, characterized in that: The micro-holes are in a semi-cut state after polishing.
3. The anti-slip and easy-to-clean tile according to claim 1, characterized in that: The glossiness of the anti-slip and easy-to-clean tiles is 28-35°.
4. The anti-slip and easy-to-clean tile according to claim 1, characterized in that: The glaze for forming the microporous glaze surface comprises the following raw materials in parts by weight: 50-55 parts of stone powder, 32-35 parts of frit, 10-12 parts of clay, and 8-9 parts of additives.
5. The anti-slip and easy-to-clean tile according to claim 1, characterized in that: The glaze for forming the microporous glaze surface comprises the following raw materials in parts by weight: 93-96 parts of non-porous glaze powder and 5-6 parts of thermal decomposition material.
6. The anti-slip easy-to-clean tile according to claim 4, characterized in that: The stone powder includes at least one of potassium feldspar, sodium feldspar, calcined talc, dolomite and quartz stone; and the clay is kaolin.
7. The anti-slip easy-to-clean tile according to claim 5, characterized in that: The thermal decomposition material is polymethyl methacrylate.
8. The method for preparing the anti-slip easy-to-clean ceramic tile according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Prepare glaze for forming the microporous glaze According to the weight composition of the glaze for forming the microporous glaze, the raw materials are mixed, ball-milled, and printing paste and printing oil are added; ball-milled again and the specific gravity is adjusted, and the mixture is sieved; S2. Glazing Using screen printing, the prepared microporous glaze is evenly printed on the surface of the body to obtain a glazed body; S3. Firing The glazed body is sent into the kiln for firing; S4. Polishing After firing, the tiles are polished to a semi-cut state.
9. The preparation method according to claim 8, characterized in that: In step S1, various raw materials are mixed and ball-milled, and the fineness after ball-milling reaches 325-350 meshes.
10. An application of non-slip and easy-to-clean tiles, characterized in that: The anti-slip and easy-to-clean ceramic tile described in any one of claims 1 to 7 or the anti-slip and easy-to-clean ceramic tile prepared by the preparation method described in any one of claims 8 to 9 is used as a decoration material and applied to the fields of home decoration, commercial places, industry, and public facilities.
Citation Information
Patent Citations
Method for preparing travertine ceramic tile with three-dimensional holes formed in part of travertine ceramic tile
CN104058784A
Anti-skid matte ceramic tile
CN109942190A
Anti-skid and anti-fouling ceramic tile with polished surface and production process and application thereof
CN113814801A
Ceramic decorative layer structure with antifouling effect
CN214144533U
Embossing floor material
JP1990157357A